Role of gut microbiota in regulating immune checkpoint inhibitor therapy for glioblastoma - Zhang, Hao; Hong, Ying; Wu, Tingting; Ben, Eyi; Li, Shuai; Hu, Liu; Xie, Tao (Frontiers in Immunology, 2024)
Glioblastoma (GBM) is a highly malignant, invasive, and poorly prognosed brain tumor. Unfortunately, active comprehensive treatment does not significantly prolong patient survival. With the deepening of research, it has been found that gut microbiota plays a certain role in GBM, and can directly or indirectly affect the efficacy of immune checkpoint inhibitors (ICIs) in various ways. (1) The metabolites produced by gut microbiota directly affect the host's immune homeostasis, and these metabolites can affect the function and distribution of immune cells, promote or inhibit inflammatory responses, affect the phenotype, angiogenesis, inflammatory response, and immune cell infiltration of GBM cells, thereby affecting the effectiveness of ICIs. (2) Some members of the gut microbiota may reverse T cell function inhibition, increase T cell anti-tumor activity, and ultimately improve the efficacy of ICIs by targeting specific immunosuppressive metabolites and cytokines. (3) Some members of the gut microbiota directly participate in the metabolic process of drugs, which can degrade, transform, or produce metabolites, affecting the effective concentration and bioavailability of drugs. Optimizing the structure of the gut microbiota may help improve the efficacy of ICIs. (4) The gut microbiota can also regulate immune cell function and inflammatory status in the brain through gut brain axis communication, indirectly affecting the progression of GBM and the therapeutic response to ICIs. (5) Given the importance of gut microbiota for immunotherapy, researchers have begun exploring the use of fecal microbiota transplantation (FMT) to transplant healthy or optimized gut microbiota to GBM patients, in order to improve their immune status and enhance their response to immunotherapy. Preliminary studies suggest that FMT may enhance the efficacy of immunotherapy in some patients. In summary, gut microbiota plays a crucial role in regulating ICIs in GBM, and with a deeper understanding of the relationship between gut microbiota and tumor immunity, it is expected to develop more precise and effective personalized immunotherapy strategies for GBM, in order to improve patient prognosis.